Ada Twist and the Disappearing Dogs - Beaty, Andrea; Roberts, David, 1970-; Naalchigar, Jennifer (New York : Amulet Books, 2022)
When pets go missing in Blue River Creek it is up to Ada to follow the scientific method by making a hypothesis, collecting data, and experimenting to find the missing animals.
Keywords: Children's questions and answers -- Juvenile fiction; Scientists -- Juvenile fiction; Questions and answers -- Fiction; Scientists -- Fiction